EVOLUTION OF USING VIRTUAL AND AUGMENTED REALITY TECHNOLOGIES IN TRAINING INFORMATICS TEACHERS - Samat, А.; Ongarbaeva, А.Д. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The article analyzes the development trends and pedagogical potential of using virtual reality (Virtual Reality) and augmented reality (Augmented Reality) technologies in the professional training of informatics teachers in recent years. The purpose of the study is to identify the evolution of applying virtual and augmented reality technologies in the process of training future informatics teachers and to determine their role in developing professional competence. The study employed content analysis and system-based methods. Over the past decade, the scope of immersive technologies in education has significantly expanded, and their integration into pedagogical training is considered an effective approach to enhancing the practical and methodological skills of pre-service teachers. Virtual and augmented reality technologies contribute to the creation of a modern learning environment that promotes students’ project-based activity, visual thinking, and digital literacy. As a result of the study, an evolutionary model for using these technologies in informatics teacher training was proposed, consisting of four stages: adaptation, application, integration, and improvement. The practical significance of the model lies in improving the efficiency of digitalizing pedagogical education and organizing immersive learning environments in higher education institutions.